Morphological and physical changes associated with growth and development of Pomegranate fruit (Indian Journal of Arid Horticulture, 2013)
Pomegranate (Punica granatum L.) is thought to  be indigenous to the region of Iran where it was first  cultivated in about 2000 B.C., but it spread to the  Mediterranean countries at a very early date. Pomegranate  is an important commercial fruit in India which is mainly  grown in the Maharashtra, Gujrath, Karnataka, Rajasthan  etc. Pomegranate flowers from late April until mid May,  whereas maturity and ripening extends from mid September to November depending on the cultivars. Fruit  growth is typically described as a single or double sigmoid  curve reflecting changes in organ fresh weight. Other  measures of growth (e.g. length, diameter) may give quite  different growth curves (Commbe, 1976).
Keywords: pomegranate; hermaphrodite; Mridula